Lumbopelvic control and the development of upper extremity injury in professional baseball pitchers - Laudner, K.; Wong, R.; Evans, D.; Meister, K. (The American Journal of Sports Medicine, 2021)
Background: The baseball-throwing motion requires a sequential order of motions and forces initiating in the lower limbs and transferring through the trunk and ultimately to the upper extremity. Any disruption in this sequence can increase the forces placed on subsequent segments. No research has examined if baseball pitchers with less lumbopelvic control are more likely to develop upper extremity injury than pitchers with more control.